Two cases of disseminated BCG disease following vaccination in the same family: case reports and review of the literature in China - Jing Wang; Qiang-Song Wu; Ming-Bo Jiang; Zhen-Hui Xu (Human Vaccines & Immunotherapeutics, 2021)
Disseminated bacillus Calmette-Guérin (BCG) disease is a rare and serious adverse event following immunization (AEFI) with BCG. Here, we reported two cases of disseminated BCG disease in the same family and reviewed the literature to identify another 35 cases in China. The average age at onset was 3.7 ± 2.1 months among the 37 cases and only 21 cases (56.8%) were laboratory confirmed. Of the 37 cases, 22 were evaluated for immunodeficiency; definite immunodeficiency was observed in 16 cases (72.7%) and could not be excluded in the other six cases (27.3%). Following treatment, 20 of the 37 cases died (54.1%), one case developed sequelae (2.7%), four cases had progressive disease (10.8%), nine cases had stable disease (24.3%), and only three cases were cured (8.1%). Vaccination of infants with BCG is cost-effective and should not be stopped because of the possibility of rare disseminated BCG disease, especially in countries with high tuberculosis burdens such as China. However, infants with a family history of immunodeficiency should be vaccinated after excluding immunodeficiency-related diseases to minimize the risk of disseminated BCG disease. Furthermore, government should strengthen proactive surveillance programs to detect and treat rare AEFIs early and improve disease outcomes.